WATERMELON FRUIT (CITRULLUS VULGARIS) AGAINST BLOOD PRESSURE FOR ELDERLY WITH HYPERTENSION - Neila Sulung; Drin Patrycia Poluan (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2015)
Introduction. Hypertension is a disorder that inhibited the supply of oxygen and nutrients to the body’s tissue inhibited and makes. The one of theraphy that can be used to control blood pressure is by eating watermelon regulary. The purpose of this study was to identify effectiveness watermelon fruit (Citrullus vulgaris) against blood pressure for elderly with hypertension. Methods. This study used Quasi Experimental design with pretest-posttest design. The numbers of samples were 12 people, that using total sampling as sampling tecnique. Analysis was performed by T-Test Dependent test. Result. Statistical analysis result showed there were any differences of blood pressure before and after treatment, with the average difference = systole 3.5mmHg and diastole 2.5mmHg. P = systole 0.000, diastole 0.049. Discussion. It can be concluded that there were any differences of giving watermelon for the blood pressure on samples with hypertention. It was highly recomanded to patients with hypertension to consume watermelon regulary.Keywords: Citrullus Vulgaris, Elderly, Hypertension